Model Wheeler dalam Mengintegrasikan Ornament Tradisi pada Kurikulum Seni - Shofi Nurhayati; Nursyirwan Nursyirwan; Mega Kencana; Suci Fajrina; Rosta Minawati (Gorga : Jurnal Seni Rupa, 2026)
This research investigates the Wheeler Model as a conceptual framework for integrating traditional ornamental elements into the art education curriculum, which is grounded in local wisdom. The study seeks to elucidate the relevance and practical application of the Wheeler Model within the context of 21st-century art learning, which prioritizes creativity, reflective thinking, and cultural awareness. A qualitative approach is employed through a library research method, involving the review and analysis of a diverse range of national and international scholarly sources pertaining to art curriculum development, culture-based education, and the preservation of traditional ornamental heritage. The findings of the study reveal that the integration of traditional ornaments within the art curriculum assumes a strategic role in sustaining cultural identity while simultaneously nurturing the creativity and cultural literacy of students. The cyclical, reflective, and adaptive Wheeler model emerges as an appropriate curriculum model due to its emphasis on the integration between learning objectives, learning experiences, material content, learning methods, and continuous reflective evaluation. Through the application of this model, art learning transcends technical proficiency, fostering cultural awareness, appreciation of aesthetic values, and critical and creative thinking abilities. The results of reflection demonstrate that the Wheeler Model effectively bridges two primary dimensions in 21st-century arts education: the preservation of local culture and the infusion of modern learning innovation. Consequently, the integration of traditional ornaments through the Wheeler Model can serve as an effective strategy for developing an art curriculum that is contextual, creative, and deeply rooted in the nation’s cultural values.